Nhận thức rủi ro trong sự chấp nhận thanh toán qua mạng xã hội (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
Social network becomes widely popular in the globe, so the association between social network and bank services is necessary. Most banks in the world have implemented e-payment service via the social network. In Vietnam, Techcombank successfully deployed this service in 2014. By investigating perceived risk in e-payment via social network adoption, this study indicates that several factors such as performance expectancy, effort expectancy, social influence, trust, and perceived risk have impacts on the e-payment via social network adoption. Not only do the results extend the Unified Theory of Acceptance and Use of Technology (UTAUT), but they should also be considered for solutions to the development of the e-payment service via the social network in Vietnam.
Keywords: E-payment via social network; Perceived risk; Technology Adoption; UTAUT